'People first' responses to an externality. Issue 3 (1st November 2022) - Lester, Ellyn A; Lester, Hugh
Abstract: Professional service firms in the built environment are subject to externalities. Whether these forces are related to economic downturns, changes in the regulatory environment, natural disasters, trade wars, armed conflict, mass migration, hyperinflation, climate change, global pandemics, entropy, or even the never foreseen, firms must adapt, reposition, and rebound from negative events. The ability to adapt is best personified by the people that make up a firm. When one firm's major commission was completely altered overnight due to the passing of major legislation that changed the mission and mandate of the agency that commissioned the work, the firm was nimble enough to pivot, make judgments about what scope could still be accomplished within the deadline, and determine who to assign the necessary tasks to get the job accomplished. The experience forced mentors to step up, mentees to step out of their comfort zones, the team to congeal under pressure, and resulted in an unmanageable deadline being met despite difficult odds and a myriad of factors beyond the firm's control. Only mentorship, knowledge sharing, resilience, and dedication allowed a positive result for the firm, the client, the user agency, and those served by the institution. It also furthered the standing perception of the firm as the trusted advisor that finds a way. This case study in the mitigation of exogenous shocks through a 'people first' strategy will highlight potential A/E/C industry responses to similar events.